Socio-economic constraints to potato production, processing, and marketing in Nigeria (2000)
Potato production is largely on smallholder farms scattered around the Plateau of northern Nigeria and concentratated particularly in areas around Jos. Yields of 4.65 tonnes per hectare obtained by smallholder farmers is about 40 percent of the potential yield. Reasons for this relatively low output are limited cultivated land, low adoption of improved practices and limited use of potato. Similarly, marketing of the crop is dominated by middlemen, to whom most of the profit accrue thereby serving as a disincentive to the .small holder farmers. There is, therefore, a need for adoption of improved production techniques, development of appropriate and affordable storage and processing technologies, more efficient distribution and marketing system and an effective extension service to improve current potato production in Nigeria.